2020
DOI: 10.1007/s40889-020-00085-0
|View full text |Cite
|
Sign up to set email alerts
|

Engaging students in ethical decision-making: a case study from an undergraduate geoscience course

Abstract: The teaching of ethics in science within the disciplines provides an avenue to deepen students' scientific understanding and to develop their critical thinking skills. This study showcases a module which connects ethics to science within a large introductory geoscience course. The module components, a tutorial plus homework assignment and an exam question, require students to decide on ethical issues using a 5-step approach that mirrors the scientific decision-making process. The assignment is graded using a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The literature review has shown that although some attempts have been made to apply a syllabus of geoethics in higher education, this is the first to do so by integrating it into different curricular units. For instance, research conducted by two esteemed scholars [23] underscores the significance of integrating ethics into science modules across various disciplines. This particular study serves as an illustrative example within the context of a comprehensive introductory geoscience course.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review has shown that although some attempts have been made to apply a syllabus of geoethics in higher education, this is the first to do so by integrating it into different curricular units. For instance, research conducted by two esteemed scholars [23] underscores the significance of integrating ethics into science modules across various disciplines. This particular study serves as an illustrative example within the context of a comprehensive introductory geoscience course.…”
Section: Introductionmentioning
confidence: 99%